Istikhdāmu Namudzajiy At-Ta’allum Istirātījiyyatu Firaq at-Tahsīl at-Thullābiyyah wa at-Ta’līm al-Qāim a‘la al-Musykilah li Tarqiyati Mahārat al-Qirāah Ladā Thullāb al-Marhalah al-Aliyah - Dony Sunarno (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2022)
Al-Izzah islamic boarding school is one of institution that is based Tahfidzul Qur'an (memorizing Qur'an) in Batu, East Java. So, the reseacher tries implement STAD method and PBL method to increase the pupils reading skills who specially to the pupils class IX of Senior High School at ALS Batu. This research is applied on 2 formulations of the problem, those are: 1. How's the using STAD method and PBL method to increase the pupils reading skills class XI of Senior High School ALS at Al-Izzah?; 2. How's increasing of reading interest Arabic text to the pupils class XI by using STAD method and PBL method?. This research intends to know using STAD method and PBL method to increase the pupils reading skills and increasing of pupils reading interest. The kind of this research is Classroom Action Research that implemented by 2 cycles. Every cycle has 4 steps, those are planning, implementation, observation, analyzing and reflection. Data is gotten from score of oral test that conducted by the researcher directly, observation, and documentation. STAD method and PBL method are very satisfying. The pupils are excited and they do not feel bored in learning process. It can be proved by the result of oral test is 86% or 26 pupils (STAD) and 93% or 28 pupils (PBL) get score 75 ore more. Then, the pupils reading interest increase, religion sibject or general lesson that can be looked from observation that conducted by the researcher.